2014
DOI: 10.1080/07315724.2013.874937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Yogurt on Fat Distribution and Gene Expression of Proinflammatory Factors in Peripheral Blood Mononuclear Cells in Overweight and Obese People with or without Weight-Loss Diet

Abstract: Our results suggested that the weight-loss diet and probiotic yogurt had synergistic effects on T-cells subset specific gene expression in PBMCs, fat percentage, and body weight among overweight and obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 37 publications
2
62
0
3
Order By: Relevance
“…Consistent to our findings, a significant reduction in MDA levels was reported in type 2 diabetic patients after consuming probiotic yogurt (Ejtahed et al, 2012). In addition, Zarrati et al (2014) showed that 8 weeks consumption of yogurt, enriched by L. acidophilus, Bifidobacterium langum , and L. casei (10 8 CFU/g each) decreased inflammatory cytokines in overweight people. In contrast, others reported no beneficial effects of probiotics on biomarkers of oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent to our findings, a significant reduction in MDA levels was reported in type 2 diabetic patients after consuming probiotic yogurt (Ejtahed et al, 2012). In addition, Zarrati et al (2014) showed that 8 weeks consumption of yogurt, enriched by L. acidophilus, Bifidobacterium langum , and L. casei (10 8 CFU/g each) decreased inflammatory cytokines in overweight people. In contrast, others reported no beneficial effects of probiotics on biomarkers of oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zarrati et al [30] examined the effects of yogurt on fat distribution and the gene expression of proinflammatory factors in peripheral blood mononuclear cells in overweight and obese individuals. They suggested that probiotic yogurt had synergistic effects on T-cell subset-specific gene expression in mononuclear cells, on the percentage of fat and on body weight in overweight and obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[15] With the fluctuations of the intestinal bacteria, probiotics can establish a balance between pro- and anti-inflammatory cytokines in the body. [16] The moderating effect of probiotics on inflammation has been approved for some inflammatory diseases, including diabetes,[17] nonalcoholic fatty liver,[18] chronic inflammation of the intestine,[1920] pregnancy,[21] rheumatoid arthritis,[22] and obesity[23] and also for patients admitted to ICUs. [24]…”
Section: Introductionmentioning
confidence: 99%